2015
DOI: 10.1002/anie.201506264
|View full text |Cite
|
Sign up to set email alerts
|

Asperchalasine A, a Cytochalasan Dimer with an Unprecedented Decacyclic Ring System, from Aspergillus flavipes

Abstract: Asperchalasine A (1), the first cytochalasan dimer featuring a unique decacyclic 5/6/11/5/5/6/5/11/6/5 ring system consisting of 20 chiral centers, was isolated from the culture broth of Aspergillus flavipes. Three biogenetically related intermediates, asperchalasines B-D (2-4), were also isolated. Their structures, including their absolute configurations, were elucidated using a combination of HRESIMS, NMR, ECD, molecular modeling, and single-crystal X-ray diffraction techniques. Compound 1, which possesses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 22 publications
4
68
0
Order By: Relevance
“…Ther elative configuration of unit A, which is similar to those of asperchalasines Band C, [10] was verified by aNOESY experiment (Figure 1e). TheN OESY cross-peaks of H-5 to H-4 and H-8, H-4 to H-10, and H-8 to Me-25 and the interactions between Me-25, H-16b,and H-19 suggested that these moieties are cofacial and b-oriented.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Ther elative configuration of unit A, which is similar to those of asperchalasines Band C, [10] was verified by aNOESY experiment (Figure 1e). TheN OESY cross-peaks of H-5 to H-4 and H-8, H-4 to H-10, and H-8 to Me-25 and the interactions between Me-25, H-16b,and H-19 suggested that these moieties are cofacial and b-oriented.…”
supporting
confidence: 65%
“…[9] In our previous study on Aspergillus flavipes cultured on rice,w ed iscovered ac ytochalasan dimer (asperchalasine A, Scheme 1). [10] Considering that the fermentation of fungi under different conditions may lead to different secondary metabolites,w ef urther investigated the metabolites of A. flavipes cultured in al iquid culture broth. In this study,t wo novel merocytochalasans,e picochalasines A( 1) and B( 2;S cheme 1), with high degrees of functionalization and intricate polycyclics tructures,w ere isolated from the liquid culture broth of A. flavipes.Compounds 1 and 2 appear to belong to the same structural family.However,because of the 1808 8 rotation of the oxidized epicoccine moiety c (Scheme 2) in 2,t heir fusion patterns differ substantially, thus resulting in different carbon skeletons.M ost notably, compounds 1 and 2 are the first examples of cytochalasan adducts characterized by an adamantyl cage in ah endecacyclic 5/6/11/5/6/5/6/5/6/6/5 ring system formed by the polymerization of an epicoccine dimer with acytochalasan moiety.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our continued investigation of bioactive metabolites from fungi, 10,11 asperterpenes A ( 1 ) and B ( 2 ), two meroterpenoids with unprecedented carbon skeletons, were isolated from the culture broth of Aspergillus terreus , along with a new biosynthetically related compound, asperterpene C ( 3 ) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1] A recent paradigm is the discovery of aseries of unprecedented fungal secondary metabolites,c ollectively termed merocytochalasans,from the fermentation broth of Aspergillus flavipes by Zhang and co-workers. [2] Structurally,a ll of these newly identified molecules consist of two types of subunits of natural origin, the tricyclic cytochalasan [3] and bicyclic epicoccine, [4] as shown in the structures of 1-13 ( Figure 1). Among them, asperchalasines B-H (1-7) [2a,e] possess aT -shaped hexacyclic skeleton consisting of one cytochalasan moiety and one epicoccine moiety,w hereas asperchalasine A ( 8) [2a] bears am ore complicated sandwich-shaped decacyclic framework containing one epicoccine moiety and two cytochalasan moieties.O ther representative merocytochalasans include asperflavipine B ( 9), [2c] epicochalasines A( 10)a nd B ( 11), [2b] and aspergilasine A ( 12), [2d] all of which comprise one cytochalasan unit and two caged epicoccine units.A sperflavipine A ( 13) [2c] is particularly notable,s ince it is the sole cytochalasan-epicoccine heterotetramer within the merocytochalasan family,w hich bears an incredibly complicated dumbbell-shaped tetradecacyclic framework.…”
mentioning
confidence: 99%